2022
DOI: 10.1177/27324745221140380
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design Principles for Multimodal Representation in Literacy Activities for Preschoolers

Abstract: The article demonstrates how to use the multimodal and multisensory representation principle of Universal Design for Learning (UDL) to increase access to storybook reading for diverse groups of preschoolers with extensive support needs (ESN). Storybook reading is an essential part of instruction in early childhood education. Utilizing UDL-inspired book boxes, children of all ability levels can partake in the activity in a meaningful manner. Multimodal representation, such as use of tangible or abstract items (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a review of recent literature, Toews and colleagues (2021) found evidence that shared reading instruction supported comprehension, vocabulary, and early literacy skill development for students with extensive support needs. Other sources have recommended shared reading instruction as a tool for developing expressive language (Towson et al, 2021) and for maintaining heritage languages and extending concepts across languages (Fundelius et al, 2023). With the increased availability of bilingual texts and the whole group style of instruction, educators can take steps before, during, and after shared reading instruction to plan inclusive lessons that strengthen language and comprehension skills in MLs who use AAC.…”
Section: Designing Inclusive Shared Reading Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of recent literature, Toews and colleagues (2021) found evidence that shared reading instruction supported comprehension, vocabulary, and early literacy skill development for students with extensive support needs. Other sources have recommended shared reading instruction as a tool for developing expressive language (Towson et al, 2021) and for maintaining heritage languages and extending concepts across languages (Fundelius et al, 2023). With the increased availability of bilingual texts and the whole group style of instruction, educators can take steps before, during, and after shared reading instruction to plan inclusive lessons that strengthen language and comprehension skills in MLs who use AAC.…”
Section: Designing Inclusive Shared Reading Instructionmentioning
confidence: 99%
“…However, teachers can supplement vocabulary instruction by using visuals, object representations, or low-tech forms of AAC during literacy lessons. Concrete and visual representations contextualize target vocabulary and scaffold understanding for learners with significant support needs (Fundelius et al, 2023) and MLs (Souto-Manning, 2016).…”
Section: Expanding Shared Reading: a Case Studymentioning
confidence: 99%